2021
DOI: 10.3390/su14010279
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Contributions to Achieving Water Sustainability: A Meta-Analytic Path Analysis of Predicting Water Conservation Behavior

Abstract: This article intends to summarize the findings of studies on the relationship between farmers’ behavioral intentions (BI) and water-conservation behavior (WCB) using the theory of planned behavior (TPB). A systematic review of transcripts obtained from Internet-based searching on reliable scientific databases (e.g., SID, ProQuest, Springer, Science Direct, John Wiley, Sage, Taylor & Francis, Emerald Insight, and Google Scholar) was followed by outfitting data for the Comprehensive Meta-Analysis (CMA) softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Nevertheless, personal norms as the feeling of ethical commitment and responsibility for drought adaptation strategies had a significant effect on their intentions. Other researchers Klöckner (2013), Biesheuvel et al (2021), Abadi and Kelboro (2022), Abid and Jie (2022) have reported a similar result. This finding points to the need for targeting people's normative influences when designing interventions in mechanisms of changing drought adaptation behaviors.…”
Section: Discussionsupporting
confidence: 66%
“…Nevertheless, personal norms as the feeling of ethical commitment and responsibility for drought adaptation strategies had a significant effect on their intentions. Other researchers Klöckner (2013), Biesheuvel et al (2021), Abadi and Kelboro (2022), Abid and Jie (2022) have reported a similar result. This finding points to the need for targeting people's normative influences when designing interventions in mechanisms of changing drought adaptation behaviors.…”
Section: Discussionsupporting
confidence: 66%
“…The hypothesis that social and personal norms reinforce farmers’ water conservation intention was supported, which corroborates with other studies. 46 , 65 , 75 , 83 This means that when designing interventions for the conservation of water resources, people's social and normative influences should be targeted. Furthermore, farmers’ water conservation attitude impacts their intention to adopt water conservation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The social sub-section refers to human interactions and relations, which can determine the outcome of resources consumption behaviour. 44 , 45 Some scholars 46 state that one of the solutions to improve water resource management is to examine the views and realities constructed by farmers of water resources and related management styles before carrying out water resource management projects. Therefore, the human-natural ecosystem relationship has recently become an integral part of policymaking and programmes for the comprehensive management of water resources, and social studies have focused on understanding human behaviour in conserving different environmental resources, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Path analysis is widely used in biological research. This method can not only analyze the relationship between independent variables and dependent variables, but also analyze the mode and degree of the influence of the indirect action between independent variables and dependent variables [27]. In this manuscript, SPSS software was used to determine the direct and indirect path coefficients of each meteorological factor to the ET 0 , so as to qualitatively study the main meteorological factors affecting the ET 0 .…”
Section: Path Analysismentioning
confidence: 99%